1996
DOI: 10.1007/978-94-017-3354-0_22
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and Source of High Altitude Glacial Deposits in the Western Alps: Clay Minerals as Saharan Dust Tracers

Abstract: Variable amounts of Saharan dust deposit on the glaciers of the Alps, fonning thin layers or mixing with local pre-existent sediments. To investigate the mineralogical composition and the source of the deposits, samples of Saharan dust, fine-grained tills and cryoconite accumulations were collected on the surface of the glaciers and/or in ice-cores. The fractionation of the samples and the bulk mineralogy allow a sharp differentiation among the different deposits. Only the clay mineralogy, however, points out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Likewise, the ash particles taken from Icelandic holes are dominantly characterized by blocky shape with stepped features and clustered clasts (Dragosics et al 2016). Moreover, angular fragments of quartz and other mineral components were detected in the coarser-grained particles (> 62µm) in cryoconite deposits of the Alps (Tomadin et al 1996).…”
Section: Glacial Grainsmentioning
confidence: 95%
See 1 more Smart Citation
“…Likewise, the ash particles taken from Icelandic holes are dominantly characterized by blocky shape with stepped features and clustered clasts (Dragosics et al 2016). Moreover, angular fragments of quartz and other mineral components were detected in the coarser-grained particles (> 62µm) in cryoconite deposits of the Alps (Tomadin et al 1996).…”
Section: Glacial Grainsmentioning
confidence: 95%
“…In newly produced grains, sharp edges, conchoidal fractures, microsteps and fracture faces prevail (Jonczak et al 2016), which may result from high-pressure fracturing during glacial transport (Immonen et al 2014;Mahaney 2002;Vos et al 2014) and local origin combined with a recent deposition (Edwards et al 2010;Tomadin et al 1996). Fresh-surfaced grains also likely reflect a severe climate conditions (Sokołowski et al 2009), which is visible, for example, through the sample from the lowest altitude (K6B), where the amount of the A-type grains is the lowest, meaning that frost weathering is less intense than in the inner part of the ice sheet.…”
Section: Glacial Grainsmentioning
confidence: 99%
“…6). However, the mineralogical composition of Saharan red dust essentially consists of residual phases (Molinaroli, 1996;Tomadin et al, 1996) as quartz and phyllosilicates (and poor plagioclase), thus explaining the different Eu anomaly in these materials.…”
Section: Atmospheric Aerosolmentioning
confidence: 98%
“…To the best of our knowledge, the first evidence of the accumulation of radionuclides in cryoconite was reported by Tomadin et al (1996), who found high levels of anthropogenic radioactivity in cryoconite samples from the European Alps. Meese et al (1997) analyzed cryoconite formed on the surface of multi-year Arctic sea ice, measuring high radioactivity values.…”
Section: Introductionmentioning
confidence: 99%